2015
DOI: 10.14520/adyusbd.62061
|View full text |Cite
|
Sign up to set email alerts
|

Fen Bi̇li̇mleri̇ Dersi̇ni̇n İlkokul Üçüncü Sinif Programina Alinmasiyla İlgi̇li̇ Öğretmen Görüşleri̇ni̇n Değerlendi̇ri̇lmesi̇

Abstract: ÖzBu araştırma 2014-2015 eğitim-öğretim

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
3
0
4
Order By: Relevance
“…Because the primary school courses carried out by the primary school classroom teachers in the 3 rd and 4rd grade science classes are the first time that students meet with science subjects, and they have an important place in their cognitive and affective learning. Therefore, it is very important for the classroom teachers who carry out these courses to perceive the concepts related to their field completely and clearly as well as being fully equipped with the knowledge of the field (Ünişen & Kaya, 2015;Tüysüz & Balıkçı, 2016).…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…Because the primary school courses carried out by the primary school classroom teachers in the 3 rd and 4rd grade science classes are the first time that students meet with science subjects, and they have an important place in their cognitive and affective learning. Therefore, it is very important for the classroom teachers who carry out these courses to perceive the concepts related to their field completely and clearly as well as being fully equipped with the knowledge of the field (Ünişen & Kaya, 2015;Tüysüz & Balıkçı, 2016).…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…Aybek and Aslan (2015), Çalışoğlu, Tortum, Erişmiş and Koçyiğit. (2015), Çiftçi, Saban, Gündüz and Olaç (2015), Ünişen and Kaya (2015) and Yıldırım and Güngör Akgün (2015) found that teachers were positive about giving science courses at the third grade level. In the first year of the Science Course, which was first offered in the 2014-2015 academic year, administering the science course at the 3rd grade can be interpreted as a positive step for the primary school science education depending on the teachers' views who are the practitioners of the curriculum.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…Öğretme-öğrenme süreci boyutunda katılımcılar programda yer alan deneyleri yapabilmek için laboratuvar ve kaynakların/materyallerin yeterli olmadığı görüşündedirler. Fen bilgisi eğitiminde kilit öneme sahip ve konuların kavratılmasında en çok tercih edilen yöntem olan deneylerin (Aykaç, Küçük, Kartal, Tilkibaş ve Keskin, 20011;Hollins ve Reiss, 2016) uygulanabilmesi gerekli laboratuvar donanımı ve okulların fiziki ve/veya finansal kaynak yetersizliği değerlendirme çalışmalarının tamamına yakınında karşımıza çıkmaktadır (Evirgen, 2013;Sıcak;Ünişen ve Kaya, 2015;Başar, 2016 vd.). Bununla birlikte bazı çalışmalarda (İzci, Özden ve Tekin, 2008) öğretme-öğrenme sürecinde deneyleri yapabilmek için zorunlu materyal gereksiniminin yüzde ellinin üzerinde karşılandığı görülmektedir.…”
Section: Sonuç Ve Tartışmaunclassified
“…Kısacası; içerik konusunda programın uygulayıcısı olan öğretmenlerin memnun olduğu sonucuna erişilmiştir. Ünişen ve Kaya (2015), Başıbeyaz (2016), Güven (2016) ve Kırındı ve Ulu' da (2017) çalışmalarında benzer sonuçlara ulaşmışlardır. Dolayısıyla 3.…”
Section: Sonuç Ve Tartışmaunclassified